Severe Maternal Morbidity in Georgia, 2009–2020. Issue 5 (11th May 2023) - Kramer, Michael R.; Labgold, Katie; Zertuche, Adrienne D.; Runkle, Jennifer D.; Bryan, Michael; Freymann, Gordon R.; Austin, David; Adams, E. Kathleen; Dunlop, Anne L.
Abstract : Background: The increasing focus of population surveillance and research on maternal—and not only fetal and infant—health outcomes is long overdue. The United States maternal mortality rate is higher than any other high-income country, and Georgia is among the highest rates in the country. Severe maternal morbidity (SMM) is conceived of as a "near miss" for maternal mortality, is 50 times more common than maternal death, and efforts to systematically monitor SMM rates in populations have increased in recent years. Much of the current population-based research on SMM has occurred in coastal states or large cities, despite substantial geographical variation with higher maternal and infant health burdens in the Southeast and rural regions. Methods: This population-based study uses hospital discharge records linked to vital statistics to describe the epidemiology of SMM in Georgia between 2009 and 2020. Results: Georgia had a higher SMM rate than the United States overall (189.2 vs. 144 per 10, 000 deliveries in Georgia in 2014, the most recent year with US estimates). SMM was higher among racially minoritized pregnant persons and those at the extremes of age, of lower socioeconomic status, and with comorbid chronic conditions. SMM rates were 5 to 6 times greater for pregnant people delivering infants <1500 grams or <32 weeks' gestation as compared with those delivering normal weight or term infants. Since 2015, SMM has increased in Georgia. Conclusion: SMM represents a collection of life-threatening emergencies that are unevenly distributed in the population and require increased attention. This descriptive analysis provides initial guidance for programmatic interventions intending to reduce the burden of SMM and, subsequently, maternal mortality in the US South.